2012
DOI: 10.1073/pnas.1210209109
|View full text |Cite
|
Sign up to set email alerts
|

Isoform-specific antagonists of exchange proteins directly activated by cAMP

Abstract: The major physiological effects of cAMP in mammalian cells are transduced by two ubiquitously expressed intracellular cAMP receptors, protein kinase A (PKA) and exchange protein directly activated by cAMP (EPAC), as well as cyclic nucleotide-gated ion channels in certain tissues. Although a large number of PKA inhibitors are available, there are no reported EPAC-specific antagonists, despite extensive research efforts. Here we report the identification and characterization of noncyclic nucleotide EPAC antagoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
149
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 128 publications
(158 citation statements)
references
References 42 publications
6
149
0
3
Order By: Relevance
“…Aliquots of stock solutions remained viable for up to 1 wk if stored frozen (Ϫ20°C) in 100% DMSO; after this time, unused drug solutions were discarded. Prior studies confirm that EPACa is a selective EPAC activator (Christensen et al 2003;Poppe et al 2008); conversely, EPACi, PKAi, and rapamycin are regarded as selective inhibitors of EPAC (Rehmann 2013;Tsalkova et al 2012), PKA (Davies et al 2000), and mTORC1 (Davies et al 2000), respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Aliquots of stock solutions remained viable for up to 1 wk if stored frozen (Ϫ20°C) in 100% DMSO; after this time, unused drug solutions were discarded. Prior studies confirm that EPACa is a selective EPAC activator (Christensen et al 2003;Poppe et al 2008); conversely, EPACi, PKAi, and rapamycin are regarded as selective inhibitors of EPAC (Rehmann 2013;Tsalkova et al 2012), PKA (Davies et al 2000), and mTORC1 (Davies et al 2000), respectively.…”
Section: Methodsmentioning
confidence: 99%
“…As shown in Fig. 5A, suppressing Epac1 activity using an Epac-specific inhibitor, ESI-09 (13,14,20), led to dose-dependent inhibition of leptin secretion. Furthermore, consistent with the pharmacological data, knocking out Epac1 in 3T3 adipocytes using the CRISPR-Cas9 gene editing system significantly suppressed leptin secretion in differentiated 3T3-L1 adipocytes (Fig.…”
Section: Aeko Mice Display Increased Body Weight and Food Intake On Hfdmentioning
confidence: 99%
“…Novel EPAC-specific inhibitors (ESI) were identified by screening a collection of 14 400 drug-like, chemically diverse small molecules ( Figure 4). [44][45][46][47] The noncyclic-nucleotide compound named ESI-08 was the first EPAC antagonist characterized and was capable of inhibiting both EPAC1 and EPAC2 activity at 25 μmol/L in the presence of equimolar concentration of cAMP ( Figure 1). 44,45 Structure-activity relationship analysis led to the identification of >2 potent EPAC antagonists designated as HJC0197 and HJC0198 with the IC50 values of 4.0 and 5.9 μmol/L, respectively ( Figure 1).…”
Section: Epac-specific Ligandsmentioning
confidence: 99%
“…[44][45][46][47] The noncyclic-nucleotide compound named ESI-08 was the first EPAC antagonist characterized and was capable of inhibiting both EPAC1 and EPAC2 activity at 25 μmol/L in the presence of equimolar concentration of cAMP ( Figure 1). 44,45 Structure-activity relationship analysis led to the identification of >2 potent EPAC antagonists designated as HJC0197 and HJC0198 with the IC50 values of 4.0 and 5.9 μmol/L, respectively ( Figure 1). 44 Further studies revealed that compounds ESI-05 and ESI-07 were isoform-specific antagonists exclusively inhibiting EPAC2 but not EPAC1; presumably by binding allosterically to the interface formed by the 2 CNBDs in EPAC2 (Figures 1 and 4).…”
Section: Epac-specific Ligandsmentioning
confidence: 99%
See 1 more Smart Citation